E0116 The cardioprotective effect of ischaemic preconditioning and the expression of adiponectin in rat myocardial ischaemic preconditioning model. (17th November 2010) - Wang, Hui; Cheng, Jingsong
Abstract : Background: A number of recent studies have reported the protective effect on ischaemic myocardial by ischaemic preconditioning (IPC) and adiponectin. Method and Result IPC model and MI model was set up. The protective effect of IPC was studied by measuring infarction size with Masson's Trichrome staining. The expression of protein and mRNA of adiponectin was examined by immunohistochemistry and quantitative real time RT-PCR o h, 6 h, 12 h and 24 h after IPC. And the plasma levels of adiponectin at four time points after IPC was also detected by ELISA. IPC reduced infarct size compared with control MI model (20±2%LV area vs 31±3%LV area, p<0.05). The expression of adiponectin mRNA 6 h and 12 h after the IPC was 2.2 and 2.1 times greater than the sham group (p<0.05) and the expression of adiponectin protein was siginificantly higher than non-ischaemic area (p<0.05). Compared to the sham groups, the plasma level of adiponectin increased significantly 0 h, 6 h and 12 h after IPC (0 h:7.40±0.47 vs 10.90±1.74;6 h:8.18±1.41 vs 10.98±1.74; 12 h:6.97±1.02 vs 9.31±0.96, p<0.05). Conclusion: Late IPC reduced infarction size and improved the expression of adiponectin mRNA and protein in myocardium, and also improved the concentration of adiponectin in plasma, which indicates that the adiponecitn may play a role in the protective effect of IPC.